2020
DOI: 10.3390/su12156225
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Environmentalism: An Emerging Economy Perspective

Abstract: Corporate environmentalism recognizes the importance of environmental issues to a corporation and how it integrates these issues into its strategy. Studies in the US and Spain have identified three variables, namely, public concern, regulatory pressures and competitive advantage to be significant in influencing corporate environmentalism. Emerging countries, although significant contributors to global environmental concerns have generally been ignored in the corporate environmentalism literature. We collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 54 publications
4
18
0
1
Order By: Relevance
“…The importance of internal and external as well as primary and secondary stakeholder groups can be treated as foundational for shaping up the environmental response of firms [61,72]. In general, the influence of stakeholders and their actions make organizations follow some specific environmental response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of internal and external as well as primary and secondary stakeholder groups can be treated as foundational for shaping up the environmental response of firms [61,72]. In general, the influence of stakeholders and their actions make organizations follow some specific environmental response.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Shahab et al [60] found CEO attributes as predictors of sustainable performance and institutionally driven environmental policies. The emphasis of top management on environmental issues make these issues more salient and can result in generating response [42,61]. In the light of the above results following hypotheses are proposed.…”
Section: Top Management Commitmentmentioning
confidence: 92%
“…Lastly, hotel guests from a developing country such as Pakistan might have a lower level of environmental awareness. Recent investigations [17,18] on customer behavior toward environmentalism in developing countries have identified customers as inconsequential stakeholders with little to no knowledge about environmental issues.…”
Section: Limitation and Future Directionsmentioning
confidence: 99%
“…Pakistan, a developing market, presents a different country-level context. The attitude and behavior of customers toward the environmental activities of firms including hotels are very different from that of customers from developed economies [17,18]. Hence, in order to better understand factors affecting the proenvironmental behavior of hotel guests, a comprehensive model using the moral norm-activation theory by Schwartz [19] and the theory of planned behavior [20] was proposed and analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Developing countries are the main suppliers and manufacturers of goods for the consumers in the developed world where social and environmental legal infrastructures are more robust; therefore, these manufacturers are compelled to adhere to policies set forth by the developed countries [37]. Compliance with local and international government regulations and industry standards has been the driving force behind the implementation of the environmental management systems in corporations working the developing world [38,39]. As a result of these social and environmental changes at the industrial and corporate levels, research related to social and environmental areas has also started gaining popularity among researchers in these emerging economies.…”
Section: Most Productive Countries Authors and Institutions And Pubmentioning
confidence: 99%